INVESTIGATION OF THE HE SOLUBILITY IN H2O-CO2 BEARING SILICATE LIQUIDS AT MODERATE PRESSURE: A NEW EXPERIMENTAL METHOD - Paonita A.; Gigli G.; Gozzi D.; Nuccio P.M.; Trigila R. (My University, 2000)
We have designed the first available experimental method capable to investigate the solubility of inert gases in H2O-CO2 bearing silicate melts in a large range of pressures. The method overcomes the difficulties imposed by the physical state of volatiles at room conditions. Experiments were done by using an internally heated pressure vessel, where sealed capsules containing the sample are introduced. The peculiarity of the method consists in the capability of loading, in accurately known proportions (even lower than ppm), volatiles in a gaseous state at room conditions. Gas is loaded as a weighed amount of a gas-bearing glass, which was previously prepared by using the same gas as a pressure medium of a superliquidus experimental run. By analyzing the gas concentration in the prepared glass, the glass itself can be used as a gas source. We applied this method in order to investigate the helium solubility in silicate melts having dissolved volatile mixtures mostly composed of H2O and CO2, in a range of pressure suitable to provide useful information regarding pre-eruptive magma degassing. Our results indicate that helium solubility is strongly affected by the H2O content in silicate liquid, displaying an increase by about a factor three as a consequence of the addition of 3 wt% H2O to the melt. Taking into account the physical mechanism of He dissolution, the sites of the silicate melt structure, where noble gases can be accommodated, drastically increase by adding modest aliquots of H2O. The influence of dissolved CO2 on helium solubility is not certain, although few signs would suggest an opposite effect with respect to H2O, at least in basalt melts. On the basis of the obtained results, we could reasonably expect that the helium behavior during the degassing of H2O-CO2 bearing magmas is sensibly different with respect to a H2O-CO2 free silicate liquid. Therefore, the effect of the major volatiles on noble gas solubility in magmas should be taken into account in the investigation of several geological processes, such as magma genesis, ascent and degassing, or mantle evolution.
Keywords: HELIUM; SOLUBILITY; SILICATE MELTS; PRESSURE; EXPERIMENTAL STUDIES